Ligand‐inducible dimeric antibody for selecting antibodies against a membrane protein based on mammalian cell proliferation. Issue 5 (26th October 2015) - Miura, Tomohiro; Nagamune, Teruyuki; Kawahara, Masahiro
ABSTRACT: A method for selecting antibodies against a membrane protein is important for attaining a variety of antibody‐based diagnostics and therapies. In this study, we propose a novel system to select specific antibodies against a membrane protein based on mammalian cell proliferation as a readout. The system employs a chimeric membrane protein in which a target membrane protein of interest is fused to the intracellular signaling domain of a cytokine receptor. The chimeric membrane protein transduces a cell proliferation signal through dimerization when co‐expressed with a specific single‐chain Fv fused with a mutant of FK‐binding protein 12 (scFv‐Fk) that can be conditionally dimerized by a synthetic ligand AP20187. To demonstrate this system, ErbB2 and gp130 were chosen as the target membrane protein and cytokine receptor, respectively. Consequently, co‐expression of the ErbB2/gp130 chimera and ErbB2‐specific scFv‐Fk rendered the cells proliferative in response to AP20187. The system also allowed selection of high‐affinity binders from a mixture composed of dominant low‐affinity binders. This system may be extended to affinity maturation of scFvs by modulating AP20187 concentration in the selection process. Biotechnol. Bioeng. 2016;113: 1113–1123. © 2015 Wiley Periodicals, Inc. Abstract : The authors demonstrate a novel system to select specific antibodies against a membrane protein based on mammalian cell proliferation as a readout. A ligand‐inducible dimeric scFv and a membrane protein/cytokine receptor chimera were designed. Co‐expression of these proteins rendered the cells proliferative in response to a dimerizer ligand. The system also allowed selection of high‐affinity binders from a mixture composed of dominant low‐affinity binders.